PENGARUH KONSEP PUNISHMENT AND REWARD DALAM PEMBELAJARAN DI SMK PEMBANGUNAN - Nurdzaki Arifin Fadhillah (Jurnal Salome : Multidisipliner Keilmuan, 2024)
The concept of punishment and reward has been proven to positively influence students' performance at the SMK Pembangunan, encouraging students to comply with rules and tasks. The main principle of compensation management is to provide suitable rewards for good performance and fair sanctions for rule violations, where punishment can effectively change students' behavior that does not meet expectations, with the goal of making the offenders feel deterred and preventing the same mistakes. The method to be used is Literature Review, aimed at collecting summaries of previous research and analyzing conclusions from experts. In the context of vocational learning at the SMK Pembangunan, literature research can be used to collect information about the influence of rewards and punishment. Literature review method helps connect theories related to the concept of punishment and reward in vocational learning in building construction and finds previous research conducted in this field. When creating the introduction for a scholarly journal, authors can use the literature review method, which should include information about the background and motivation of the article, the latest developments in the focus area, as well as research gaps and innovations. Tools such as internet journals can be used when conducting the literature review. Literature research findings indicate a positive correlation between reward and the level of student discipline at the SMK Pembangunan. Mufidah's study (2012) supports this finding, revealing that providing economic tokens periodically can significantly alter students' disciplined behavior. Regular and appropriate rewards can be an essential component in shaping and enhancing student discipline. Rewards play a significant role in changing student behavior, with regular recognition or appreciation of desired behavior encouraging students to maintain or improve it, thus helping to build a positive relationship between students and teachers and instilling better behavior patterns both inside and outside the classroom.